Pengaruh Komunikasi Pemasaran Terpadu terhadap Tingkat Kunjungan Wisatawan Domestik pada Wisata Pantai Sari Ringgung di Kabupaten Pesawaran Lampung Selatan - Prayogo, Agung; Baskoro, Ery (Universitas Muhammadiyah Metro, 2021)
Based on the field findings, it is found that the problems that occur are the decrease in the level of tourist visits at Sari Rutut Beach on weekdays, and the lack of success in increasing tourism objects due to ineffective promotions. The purpose of this study was to determine the effect of advertising and promotion on the level of domestic tourist visits to Sari Rutut Beach in Pesawaran Regency. This research is a quantitative research. With this type of explanatory survey research, and advertising and promotion as independent variables and the level of domestic tourist visits as the dependent variable. The technique of determining the sample is accidental sampling, as many as 73 visitors were met at the time of the study. As a measurement tool used 60 questionnaire items with Likert scale measurement and analyzed using multiple linear regression. Methods of data collection by observation, interviews, questionnaires and documentation. The results of the study using the t test (partial) showed the value of the effect of advertising on the level of tourist visits, namely tcount> ttable (1.673 1.669), and the value of the effect of promotion on the level of tourist visits, namely tcount> t table (2.606 1,669). While the f test (simultaneous) shows the value of the effect of advertising and promotion simultaneously on the level of tourist visits, namely fcount> ftabel (11.284> 3.737). From the calculation of the R square value, the ability of the independent variable to explain the variance of the dependent variable is 63.5%, which means that 36.5% of the variance of the dependent variable is explained by other factors not examined.